2019
DOI: 10.1111/joa.12992
|View full text |Cite
|
Sign up to set email alerts
|

Disconnecting bones within the jaw‐otic network modules underlies mammalian middle ear evolution

Abstract: The origin of the mammalian middle ear ossicles from the craniomandibular articulation of their synapsid ancestors is a key event in the evolution of vertebrates. The richness of the fossil record and the multitude of developmental studies have provided a stepwise reconstruction of this evolutionary innovation, highlighting the homology between the quadrate, articular, pre-articular and angular bones of early synapsids with the incus, malleus, gonial and ectotympanic bones of derived mammals, respectively. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 84 publications
(293 reference statements)
1
6
0
Order By: Relevance
“…Beside the ontogenetic signal in network parameters, many taxa in our sample, including non-avian theropods, show a leftright asymmetry in modularity, which is caused when paired bones are assigned to different modules or unpaired bones do not form their own module, but are assigned either to a left or right module. Similar asymmetries were previously found in skull network analyses of amniote and synapsid skulls 11,31 and the skull muscularity of primates and deformed humans 32,33 . On the Fig.…”
Section: Adult Birds Vs Na-archosaurssupporting
confidence: 83%
“…Beside the ontogenetic signal in network parameters, many taxa in our sample, including non-avian theropods, show a leftright asymmetry in modularity, which is caused when paired bones are assigned to different modules or unpaired bones do not form their own module, but are assigned either to a left or right module. Similar asymmetries were previously found in skull network analyses of amniote and synapsid skulls 11,31 and the skull muscularity of primates and deformed humans 32,33 . On the Fig.…”
Section: Adult Birds Vs Na-archosaurssupporting
confidence: 83%
“…Rather, the functional differences observed here are more nuanced and specific to individual anatomical regions, suggesting that the cranial skeleton underwent a selective reorganisation. Such modular evolution of the vertebrate skeleton has been demonstrated to constitute an important factor in mammals: 19 developmental 20,21 , molecular 22,23 and morphological [24][25][26] studies have found evidence for a semiautonomous trait evolution of mammalian cranial regions. In particular, interconnected anatomical and functional modularity was found to be present in the evolution of the mammalian middle ear due to a reduction in cranial complexity 26 .…”
Section: Discussionmentioning
confidence: 99%
“…It would seem that there is much evolvability in the modularity of middle ear structures in mammals throughout development and that adult structures of different developmental origins may operate as modules. Anatomical modules had been identified in the synapsid evolution leading to the DMME (Navarro-Díaz et al 2019;Mao and Meng 2020). Modularity, not surprisingly, exists in both the phylogeny and ontogeny of the jaw/middle ear structures of mammals.…”
Section: Discussionmentioning
confidence: 99%
“…The disappearance of Meckel's cartilage may have occurred independently in numerous mammalian lineages from the Late Jurassic to the Late Cretaceous, whereas detachment of what became the middle ear bones from the postdentary trough may have occurred once each in the ancestors of therians and monotremes (Ramírez-Chaves et al 2016). The study of the morphological transformation leading to the DMME in ontogeny and phylogeny can be approached from a conceptual perspective of modularity and evolvability (Navarro-Díaz et al 2019;Le Maître et al 2020).…”
Section: Introductionmentioning
confidence: 99%